Quantum calculation of transition probabilities, cross sections and thermal rate constant for the H++LiH(vj) inelastic scattering - Akpinar, Sinan; Gogtas, Fahrettin (Elsevier, 2006)
Time-dependent wave packet calculations were carried out to study the H+ + LiH inelastic scattering. The state-to-state and state-to-all transition probabilities for total angular momentum J=0 have been calculated. The probabilities for J > 0 are estimated from the J=0 results by using J-shifting approximation based on a capture model. Then, the integral cross sections and thermal rate constants are calculated. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: inelastic scattering; reaction dynamics; wavepacket study